PENILAIAN RISIKO BENDUNGAN SAGULING DENGAN METODE TRADISIONAL, METODE POHON KEJADIAN DAN METODE MODIFIKASI ICOLD - Riksal Firmansyah; Ignatius Sriyana (Wahana Teknik Sipil: Jurnal Pengembangan Teknik Sipil, 2022)
The role of dam infrastructure must be ensured from management and maintenance through good operational and maintenance provisions as to maintain level of service provision, extend life of productive assets and reduce risk of dam failure. Dam risk assessment can be used to prioritize dams based on risks. Risk assessment consists of risk analysis and risk evaluation. Purpose of this study is to conduct a risk assessment on Saguling Dam using traditional methods, event tree methods and ICOLD modification method to get an overview safety condition Saguling Dam. In conducting risk evaluation for ICOLD modification method, evaluate by comparing value of risk index to risk class. results of the risk identification analysis of this study that risk assessment using traditional method shows that risk of the Saguling Dam is unacceptable because this method does not describe each possibility in detail. Risk assessment using the event tree method shows that the risk of the Saguling Dam is acceptable. Risk assessment using the modified ICOLD method shows that the Saguling Dam belongs to category of Dam with moderate risk.